Home on the digital range: range-related Web outreach and ranchers' internet use - Ghajar, Shayan, author; Fernández-Giménez, Maria E., advisor; Meiman, Paul, committee member; Vaske, Jerry, committee member (Colorado State University. Libraries, 2014)
Access to the internet continues to improve in rural areas, ensuring ranchers will have increasing opportunities to use the Web to find information about management practices that may provide ecological and financial benefits to their ranches. While past studies have examined the role of the internet in informing daily decision-making by agricultural producers, no studies have focused specifically on describing and analyzing the use of the internet by ranchers in the Western United States. This study uses a mixed-methods approach to assess the extent and patterns of ranchers' internet use in Colorado and Wyoming, identify barriers to greater use, and establish a typology of Web use behavior by ranchers. We also assess a sample of current range-related websites by measuring the presence or absence of features and characteristics shown by past research to enhance potential impacts on site visitors. Our findings indicate that internet use is widespread, and that age, education, and risk tolerance can predict the extent to which a rancher will rely on the internet for day-to-day ranch management. A cluster analysis delineated four separate Web usage typologies among ranchers with which outreach personnel can determine the potential utility of digital outreach tools for their programming based on their target audience and topics of outreach. The website assessment found that educational sites in our sample could improve their potential perceived credibility and their potential impact on visitors' attitudes by using testimonials and quotations more frequently. Based on these findings, we recommend that rangeland outreach personnel determine the potential benefits of incorporating online outreach depending on which typology or typologies of Web-using ranchers they are targeting. Additionally, range-related websites should attempt to incorporate as many message characteristics and structural features as possible to maximize their potential perceived credibility by website visitors, and to increase their potential for altering their attitudes about a topic.